Pengaruh Kombinasi Tapioka dan Bahan Pengenyal dalam Pembuatan Galantin Ikan Kembung Rendah Limbah - Lasmi Latu, Priska Sulfiaster; Mushollaeni, Wahyu; Wirawan, Wirawan (JASATHP: Jurnal Sains dan Teknologi Hasil Pertanian, 2025)
East Manggarai in East Nusa Tenggara Province has rich marine resources and abundant productivity. One of the marine commodities is mackerel (Rastrelliger kanagurta). Currently, especially in East Nusa Tenggara, mackerel is primarily used as a side dish and processed into local food products. However, given its complete nutritional content, mackerel has the potential to be developed into a raw material for healthy food products that benefit human health. This research aims to determine the best treatment for the use of firming agents and their concentrations in the production of mackerel fish galantine. This study used a Randomized Block Design (RBD) with two factors: type of firming agent (CMC, carrageenan, agar) and concentration (1%, 2%, 3%). The tests conducted included calcium content, texture, and L* value (brightness) of the galantine. The best treatment was the use of CMC as a firming agent at a concentration of 3%. This formula produced mackerel fish galantine with a calcium content of 313.40 ppm, texture value of 12.20 N, brightness value (L) of 18.06, and an average preference test result of "like" (texture 2.68, taste 2.63, color 2.60, and aroma 2.73).